Answer :

Using the identity x^{2} – y^{2} = (x + y)(x – y)

⇒ (a + b)(a – b) = 11 × 9

Since 11 is a prime number therefore the factors can be equated,

⇒ a + b = 11

And a – b = 9

On solving above two equations we get,

a = 10 and b = 1

Rate this question :

How useful is this solution?

We strive to provide quality solutions. Please rate us to serve you better.

Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Expertsview all courses

Dedicated counsellor for each student

24X7 Doubt Resolution

Daily Report Card

Detailed Performance Evaluation

RELATED QUESTIONS :

Let us check the West Bengal Mathematics

Let us factorise West Bengal Mathematics

Let us calculate West Bengal Mathematics

The value of 25<sWest Bengal Mathematics

Short answer typeWest Bengal Mathematics

Short answer typeWest Bengal Mathematics

Short answer typeWest Bengal Mathematics

If a + b + c = 0,West Bengal Mathematics

Let us factorise West Bengal Mathematics

Short answer typeWest Bengal Mathematics